Internalization Internalization of Tolerance Values through Akidah Akhlak Learning at MAN 1 Pringsewu and MA Darul Ulum - Mz, Riza Arif; Basri Basri; Ahmad Barizi (Pusat Riset dan Inovasi Nasional, 2024)
The lack of integration of tolerance and multiculturalism education has resulted in the continued prevalence of intolerant and radical attitudes among society and the younger generation.This study aims to describe the implementation and internalization process of tolerance values ​​through Akidah Akhlak learning at MAN 1 Pringsewu and MA Darul Ulum and to identify its impact on students' attitudes. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that MAN 1 Pringsewu emphasized cognitive and affective approaches in tolerance learning, such as through the delivery of material